Impact of liver graft steatosis on long-term post-transplant hepatic steatosis and fibrosis via magnetic resonance quantification - Mak, Lung-Yi; Fung, James; Lo, Gladys; Lo, Christine Shing-Yen; Wu, Trevor Kwan-Hung; Chung, Matthew Shing-Hin; Wong, Tiffany Cho-Lam; Seto, Wai-Kay; Chan, Albert Chi-Yan; Yuen, Man-Fung (Frontiers in Medicine, 2025)
BackgroundThe rising prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) has led to an increased occurrence of steatotic liver grafts (SLG) in liver transplantation (LT). However, the implications of SLG on post-transplant de novo hepatic steatosis (PTHS) and advanced fibrosis (≥F3) remain uncertain. This study aimed to characterize PTHS and ≥ F3 using magnetic resonance imaging (MRI) in patients who underwent LT for non-MASLD indications and to examine their relationship with SLG.MethodsPost-LT patients with implant biopsy fat content data were recruited for MRI assessments. MRI-proton density fat fraction (MRI-PDFF) and MR elastography (MRE) were performed using a 1.5 Tesla Optima 450 W MR scanner with a 3D volumetric sequence. PTHS and ≥ F3 were defined as MRI-PDFF ≥5% and MRE ≥3.64 kPa, respectively. SLG was defined as implant biopsy fat content ≥5%.ResultsA total of 292 patients (70.5% men, median age at LT: 51.9 years, 22.6% with SLG) were recruited. The majority (73.6%) were transplanted for hepatitis B virus (HBV)-related complications. MRI performed at a median of 12.2 years post-LT identified PTHS in 27.4 and 10.6% of patients. PTHS was independently associated with SLG (OR 2.067, 95% CI 1.082–3.951), central obesity (OR 3.952, 95% CI 1.768–8.832), and hypertension (OR 2.510, 95% CI 1.268–4.966). In contrast, ≥F3 was associated with sex, change in BMI, and abnormal liver biochemistry but not with PTHS or SLG.ConclusionMRI identified a high prevalence of PTHS, which was associated with SLG and metabolic risk factors among Chinese patients transplanted for non-MASLD indications. Advanced graft fibrosis was not associated with PTHS or SLG.